Виокремлення спільнокореневих неологізмів у лексиконі письменника (на матеріалі корпусу текстів Євгена Пашковського) - Дюндик, О. (Лексикографічний бюлетень, 2016)
У цій статті здійснимо опис неологізмів зі спільним коренем «вовк/вовч», які ми відшукали в корпусі текстів Є. Пашковського. The article describes method of common-rooted neologisms extraction in writer`s lexicon (based on the text corpora of Yevhen Pashkovsky’s novels). The concordance of words with the common root “wolf ” has been formed automatically, neologisms is distinguished in it, its structural description and semantic interpretation have been made. The significance of the symbol “wolf ” in Ukrainian folklore and its place in the novels of E. Pashkovsky is traced.